Study on heath forest species of Melaleuca cajuputi as potential natural herbicide agent to suppress weed growth in landscape maintenance management - Othman, Rashidi; Wan Daud, Wan Masyitah; Ramya, Razanah; Johari, Nursyafica Nadia; Hj. Baharuddin, Zainul Mukrim (IOP Publishing, 2019)
Weeds are diverse in their habit and habitats throughout the world. In landscape management, weeds are of concern because they compete with other plants for growth factors. Modern management nowadays relies on the importance of synthetic chemicals to control weeds as unwanted plants in order to reduce the weed management cost. The use of herbicides does not represent an appropriate tool for the control of some weeds developing but leading negatively affect the environment. Managing the landscape and natural resources are not only designing good views and environment but also upgrading and maintaining it through a good consideration to ensure the living environment. Therefore, this study aimed to explore Melaleuca cajuputi of heath forest species as potential natural herbicides agent in sustainable landscape management. Three assessments were conducted in order to determine their effectiveness towards suppressing weeds without degrading the environmental quality index. Assessment of physicochemical properties of soil and water, as well as allelochemical compounds, demonstrated that these species having allelopathic potential as a natural herbicide.